Cold-rolled martensitic steel and method for producing same

By adjusting the chemical composition and heat treatment process of the martensite steel plate, a high-strength, good formability and high porosity martensite steel plate is formed, which solves the problem of the increase in the strength of the steel plate in the prior art, and realizes the automobile The dual requirements for strength and formability of components.

CN119137303APending Publication Date: 2024-12-13ARCELORMITTAL SA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202280095609.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-08-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to find martensite steel plates with high strength, good formability and high porosity in automotive parts, and the increase in strength of the steel plate will lead to a decrease in forming properties, which cannot satisfy both the strength and formability of automotive parts. Require.

Method used

By adjusting the chemical composition and heat treatment process of the steel plate, martensite steel containing 0.07%-0.12%, manganese 1.9%-2.5%, silicon 0.2%-0.6%, chromium 0.1%-0.5% and other elements were prepared, combined with specific The hot rolling and cold rolling process forms 80%-94% tempered martensite and 6%-20% fresh martensite microstructure to achieve high strength and good formability of the steel plate.

Benefits of technology

Martensite steel plate with an ultimate tensile strength greater than 960MPa, a yield strength greater than 700MPa, and a porosity retractability of 40% or greater was obtained. It has good forming suitability and weldability, and is suitable for automotive parts manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005111979170000081
    Figure BDA0005111979170000081
  • Figure BDA0005111979170000091
    Figure BDA0005111979170000091
  • Figure BDA0005111979170000101
    Figure BDA0005111979170000101
Patent Text Reader

Abstract

A martensitic steel sheet comprising the following elements: 0.07% < = C < = 0.12%; 1.9% < = Mn < = 2.5%; 0.2% < = Si < = 0.6%; 0.01% < = Al < = 0.1%; 0.1% < = Cr < = 0.5%; 0.2% < = Mo < = 0.6%; 0% < = S < = 0.09%; 0% < = P < = 0.09%; 0% < = N < = 0.09%; 0.001% < = Ti < = 0.1%; 0.0005% < = B < = 0.005%; 0% < = Nb < = 0.1%; 0% < = V < = 0.1%; 0% < = Ni < = 1%; 0% < = Cu < = 1%; 0% < = Sn < = 0.1%; 0% < = Pb < = 0.1%; 0% < = Sb < = 0.1%; 0.001% < = Ca < = 0.01%; the remainder consists of iron and inevitable impurities resulting from processing, the microstructure of the steel consisting of, in area percentage, 80% to 94% of tempered martensite and 6% to 20% of fresh martensite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing cold rolled martensitic steel suitable for the automotive industry, and in particular to martensitic steel having a tensile strength of 960 MPa or more. Background Art

[0002] Auto parts need to meet two inconsistent requirements, namely, easy formability and strength, but in recent years, in consideration of global environmental issues, a third requirement of improving fuel consumption has been given to automobiles. Therefore, currently, auto parts must be made of materials with high formability to meet the standard of easy assembly of complex automotive components, and at the same time, strength must be improved for vehicle crashworthiness and durability, while reducing the weight of the vehicle to improve fuel efficiency.

[0003] Therefore, a great deal of research and development efforts have been invested to reduce the amount of material used in automobiles by increasing the strength of the material. Conversely, an increase in the strength of a steel sheet reduces formability, and therefore there is a need to develop a material having both high strength and high formability.

[0004] Early research and development in the field of high strength and high formability steel sheets has resulted in several methods for producing high strength and high formability steel sheets, some of which are listed herein for a clear understanding of the present invention:

[0005] EP3901299 provides a cold-rolled steel sheet, a hot-dip galvanized steel sheet, a hot-dip galvannealed steel sheet and a method for manufacturing the same having excellent workability, wherein the cold-rolled steel sheet contains, by weight%, 0.06% to 0.15% carbon (C), 1.2% or less silicon (Si) (excluding 0), 1.7% to 2.7% manganese (Mn), 0.15% or less molybdenum (Mo) (excluding 0), 1.0% or less chromium (Cr) (excluding 0), 0.1% or less phosphorus (P), 0.01% or less sulfur (S), 0.001% to 0.04% titanium (Ti), 0.001% to 0.04% niobium (Nb), 0.01% or less nitrogen (N), 0.01% or less boron (B) (excluding 0), and the balance Fe and other inevitable impurities, wherein the amounts of silicon (Si), carbon (C), manganese (Mn), molybdenum (Mo) and chromium (Cr) in the matrix structure at a point of thickness of 1 / 4t satisfy the following relationship 1, the microstructure contains, by area%, 10% to 70% of ferrite, 10% to 50% of bainite and residual austenite as the sum thereof, and the balance fresh martensite, and the ratio (Mb / Mt) of the fraction (Mt) of the total fresh martensite and the fraction (Mb) of the fresh martensite adjacent to the bainite is 60% or more. [Relationship 1] ([Si] + [C] × 3) / ([Mn] + [Mo] + [Cr]) ≥ 0.18 ([Si], [C], [Mn], [Mo] and [Cr] are the weight % of silicon (Si), carbon (C), manganese (Mn), molybdenum (Mo) and chromium (Cr) at a point of 1 / 4t thickness of the cold-rolled steel sheet, respectively). However, the steel of EP3901299 does not exhibit a hole expansion rate of 40% or more. Summary of the invention

[0006] The object of the present invention is to solve these problems by making available a cold rolled martensitic steel sheet having simultaneously:

[0007] - an ultimate tensile strength greater than or equal to 960 MPa and preferably greater than 1000 MPa,

[0008] - a yield strength greater than or equal to 700 MPa and preferably greater than 720 MPa,

[0009] - A hole expansion ratio of 40% or more and preferably 45% or more.

[0010] Preferably, such a steel may also have good formability (for rolling) as well as good weldability and paintability.

[0011] Another object of the invention is also to make available a method for manufacturing these panels that is compatible with conventional industrial applications while being robust to variations in manufacturing parameters. DETAILED DESCRIPTION

[0012] The above objects and other advantages of the present invention will become more apparent through detailed description of preferred embodiments of the present invention.

[0013] The chemical composition of cold rolled martensitic steel contains the following elements:

[0014] Carbon is present in the steel of the present invention at 0.07% to 0.12%. Carbon is an element necessary to improve the strength of the steel of the present invention by producing a low temperature transformation phase such as martensite. A carbon content of less than 0.07% will not impart tensile strength to the steel of the present invention. On the other hand, at a carbon content exceeding 0.12%, the steel exhibits poor spot weldability, which limits its application for automotive parts. The preferred content of the present invention can be maintained at 0.08% to 0.11%, and more preferably 0.09% to 0.11%.

[0015] The manganese content of the steel of the present invention is 1.9% to 2.5%. This element promotes austenite formation. Manganese provides solid solution strengthening and reduces the ferrite transformation rate, thus contributing to the formation of martensite. An amount of at least 1.9% is required to impart strength and contribute to the formation of martensite. However, when the manganese content is greater than 2.5%, it has an adverse effect, for example, it hinders the transformation of austenite to martensite during cooling after annealing. A manganese content greater than 2.5% may excessively segregate in the steel during solidification and impair the homogeneity inside the material, which may lead to surface cracks during the hot working process. The preferred limit of the presence of manganese is 2% to 2.4%, and more preferably 2.1% to 2.35%.

[0016] The silicon content of the steel of the present invention is 0.2% to 0.6%. Silicon is an element that contributes to improving strength by solid solution strengthening. Silicon is a component that can slow down the precipitation of carbides during cooling after annealing, and therefore, silicon promotes the formation of martensite. But silicon is also a ferrite forming element, and also increases the Ac3 transformation point, which pushes the annealing temperature to a higher temperature range, which is why the silicon content is kept at a maximum of 0.6%. A silicon content greater than 0.6% may also cause temper embrittlement, and in addition, silicon also impairs coatability. The preferred limit of silicon presence is 0.25% to 0.5%, and more preferably 0.25% to 0.4%.

[0017] The chromium content of the steel of the present invention is 0.1% to 0.5%. Chromium is an essential element that provides strength to the steel by solid solution strengthening, and a minimum of 0.1% is required to impart strength, but the surface finish of the steel is impaired when more than 0.5% is used. The preferred limit of chromium presence is 0.15% to 0.4%, and more preferably 0.15% to 0.35%.

[0018] The content of aluminum is 0.01% to 0.1%. In the present invention, aluminum removes oxygen present in molten steel to prevent oxygen from forming a gas phase during the solidification process. Aluminum also fixes nitrogen in steel to form aluminum nitride to reduce the size of grains. Higher aluminum content (greater than 0.1%) increases the Ac3 point to a high temperature, thereby reducing productivity. The preferred limit of aluminum presence is 0.01% to 0.09%.

[0019] Molybdenum is an essential element constituting 0.2% to 0.6% of the steel of the present invention; Molybdenum plays an effective role in improving hardenability and hardness, delaying the appearance of bainite and thus promoting the formation of martensite, especially when added in an amount of at least 0.2%. However, the addition of molybdenum excessively increases the addition cost of the alloying element, so that its content is limited to 0.6% for economic reasons. The preferred limit of the presence of molybdenum is 0.25% to 0.5%, and more preferably 0.25% to 0.4%.

[0020] Niobium is present in the steel of the invention in the range of 0.001% to 0.1% and is suitable for forming carbonitrides to give additional strength to the steel of the invention by precipitation hardening. Niobium will also influence the size of the microstructural components by its precipitation as carbonitrides and by hindering recrystallization during the heating process. Thus, the finer microstructure formed at the end of the holding temperature and therefore after full annealing will lead to hardening of the product. However, niobium contents greater than 0.1% are not economically interesting because a saturation effect of its influence is observed, which means that additional amounts of niobium do not lead to any strength improvement of the product.

[0021] Sulfur is not an essential element but may be contained in the steel as an impurity, and from the viewpoint of the present invention, it is preferred that the sulfur content is as low as possible, but from the viewpoint of manufacturing cost, the sulfur content is 0.09% or less. In addition, if higher sulfur is present in the steel, it combines with manganese in particular to form sulfides and reduces its beneficial effects on the present invention.

[0022] The phosphorus content of the steel of the present invention is 0% to 0.09%. Phosphorus reduces spot weldability and hot ductility, especially due to its tendency to segregate at grain boundaries or co-segregate with manganese. For these reasons, its content is limited to 0.09%, and preferably below 0.06%.

[0023] Nitrogen is limited to 0.09% to avoid ageing of the material and to minimize precipitation of aluminium nitride during solidification which is detrimental to the mechanical properties of the steel.

[0024] Titanium is an alloying element and can be added to the steel of the present invention at 0.001% to 0.1%. It forms titanium-nitride and prevents B from entering the solution during steelmaking. The amount of titanium is therefore limited to 0.1% to avoid the formation of coarse titanium-nitrides that are detrimental to formability. In the case where the titanium content is less than 0.001%, no effect is imparted to the steel of the present invention.

[0025] Boron is an alloying element for the steel of the present invention and may be present in an amount of 0.0005% to 0.005%. When added in an amount of at least 0.0005%, boron can improve the hardenability of the steel during cooling, which can avoid the formation of soft phases and promote the formation of hard martensite in the final microstructure.

[0026] Vanadium is an optional element of the steel of the present invention. Vanadium is effective in improving the strength of steel by forming carbides or carbonitrides, and from an economical point of view, the upper limit is 0.1%.

[0027] Nickel can be added as an optional element in an amount of 0% to 1% to increase the strength of the steel of the present invention and improve its toughness. A minimum of 0.01% is preferred to obtain such effects. However, when its content is greater than 1%, nickel causes deterioration of ductility.

[0028] Copper can be added as an optional element in an amount of 0% to 1% to increase the strength of the steel of the present invention and improve its corrosion resistance. A minimum of 0.01% is preferred to obtain such effects. However, when its content is greater than 1%, it may deteriorate the surface appearance.

[0029] Calcium can be added to the steel of the present invention in an amount of 0.001% to 0.01%. Calcium is added to the steel of the present invention as an optional element, especially during inclusion treatment. Calcium aids in the refining of steel by binding harmful sulfur contents in the form of globules, thereby hindering the harmful effects of sulfur.

[0030] Other elements such as Sn, Pb or Sb can be added alone or in combination in the following proportions: Sn≦0.1%, Pb≦0.1% and Sb≦0.1%. Up to the maximum content levels shown, these elements allow grain refinement during solidification. The remainder of the steel composition consists of iron and unavoidable impurities resulting from processing.

[0031] The microstructure of the martensitic steel plate will now be described in detail, with all percentages being area fractions.

[0032] Tempered martensite constitutes 80% to 94% of the microstructure by area fraction. Tempered martensite is formed by martensite formed during cooling after annealing and in particular within a temperature range of Ms-100°C to Ms, and more particularly Ms-70°C to Ms. Such martensite is then tempered during a tempering temperature Ttempering maintained at 400°C to 550°C. The tempered martensite of the present invention imparts ductility and strength to such steel. Preferably, the content of tempered martensite is 84% ​​to 94%, and more preferably 85% to 94%.

[0033] Fresh martensite constitutes 6% to 20% of the microstructure by area fraction. The steel of the present invention forms fresh martensite due to cooling after the tempering holding of the cold-rolled steel sheet. Martensite imparts ductility and strength to the steel of the present invention. However, when the presence of fresh martensite is greater than 20%, it imparts excessive strength but reduces the hole expansion rate, exceeding the acceptable limit of the steel of the present invention. Since fresh martensite contains a large amount of carbon, it is brittle and hard, so the preferred limit of fresh martensite of the steel of the present invention is 6% to 18%, and more preferably 6% to 15%.

[0034] The microstructure of the cold-rolled martensitic steel sheet does not contain microstructure components such as ferrite, bainite, retained austenite, pearlite, and cementite in addition to the above-mentioned microstructure.

[0035] The steel according to the invention can be manufactured by any suitable method. However, as a non-limiting example, it is preferred to use the method according to the invention which will be described in detail.

[0036] Such a preferred method consists in providing a semi-finished casting of steel having the chemical composition of the initial steel according to the invention. The casting can be made into an ingot or continuously made into the form of thin slabs or thin strips, i.e., the thickness ranges from about 220 mm for slabs to tens of millimeters for thin strips.

[0037] For example, a slab having a chemical composition according to the invention is produced by continuous casting, wherein the slab is optionally subjected to direct soft reduction during the continuous casting process to avoid center segregation and ensure that the ratio of local carbon to nominal carbon remains below 1.10. The slab provided by the continuous casting process can be used directly at high temperature after continuous casting, or can be first cooled to room temperature and then heated for hot rolling.

[0038] The temperature of the slab subjected to hot rolling must be at least 1000°C and must be lower than 1280°C. In the case where the temperature of the slab is lower than 1000°C, an excessive load is imposed on the rolling mill, and furthermore, the temperature of the steel may be reduced to the ferrite transformation temperature during the finish rolling, so that the steel will be rolled in a state containing transformation ferrite in the structure. Therefore, the temperature of the slab must be high enough so that the hot rolling should be completed in the temperature range of Ac3 to Ac3+100°C. Reheating at a temperature higher than 1280°C must be avoided because it is industrially expensive.

[0039] The plate obtained in this way is then cooled at a cooling rate of at least 10° C. / second to a coiling temperature which must be below 675° C. Preferably, the cooling rate will be less than or equal to 200° C. / second.

[0040] The hot rolled steel sheet is then coiled at a coiling temperature below 675° C. to avoid ovalization, and preferably coiled at 475° C. to 625° C. to avoid scale formation, wherein a more preferred range of such coiling temperature is 500° C. to 660° C. The coiled hot rolled steel sheet is then cooled to room temperature and then subjected to optional hot strip annealing.

[0041] The hot rolled steel sheet may be subjected to an optional descaling step to remove the scale formed during hot rolling prior to the optional tropical annealing. The hot rolled sheet may then be subjected to an optional tropical annealing. In a preferred embodiment, such tropical annealing is carried out at a temperature of 400° C. to 750° C., preferably for at least 12 hours and not more than 96 hours, the temperature preferably being kept below 750° C. to avoid partially transforming the hot rolled microstructure and, therefore, possibly losing microstructural homogeneity. Thereafter, the optional descaling step of the hot rolled steel sheet may be carried out, for example, by pickling of such sheet.

[0042] The hot-rolled steel sheet is then subjected to cold rolling at a thickness reduction rate of 35% to 90% to obtain a cold-rolled steel sheet.

[0043] The cold rolled steel sheet is then subjected to a heat treatment which imparts the necessary mechanical properties and microstructure to the steel of the present invention.

[0044] The cold rolled steel sheet is heated to an soaking temperature T of Ac3 to Ac3+100°C, and preferably Ac3 to Ac3+50°C, at a heating rate HR1 of at least 1°C / s, and preferably greater than or equal to 2°C / s, wherein Ac3 of the steel sheet is calculated by a dilatometric study according to ASTM A1033-18 standard.

[0045] The cold rolled steel sheet is held at Tsoak for a period of 10 to 500 seconds to ensure complete recrystallization and complete transformation of the heavily work-hardened initial structure into austenite.

[0046] The cold rolled steel sheet is then soaked and cooled from T to a temperature T1 in the range of Ms-100°C to Ms at a cooling rate CR1 of 1°C / sec to 150°C / sec. In a preferred embodiment, the cooling rate CR1 for such a cooling step is 20°C / sec to 120°C / sec. The preferred T1 temperature for such a first step is Ms-70°C to Ms. The cold rolled steel sheet is then held at T1 for a time of 5 seconds to 100 seconds, and preferably 5 seconds to 50 seconds, and more preferably 5 seconds to 30 seconds.

[0047] The Ms of the steel plate was calculated by using dilatometry studies according to ASTM A1033-18 standard.

[0048] Thereafter, the cold rolled steel sheet is reheated to a tempering temperature Ttemper of 400° C. to 550° C. for a time of 10 to 600 seconds at a heating rate of at least 1° C. / sec, and preferably at least 2° C. / sec, and more preferably at least 10° C. / sec. The preferred temperature range for tempering is 420° C. to 500° C., and the preferred duration for holding at Ttemper is 20 to 300 seconds.

[0049] The cold rolled martensitic steel sheet of the present invention may be optionally coated with zinc or zinc alloy, or with aluminum or aluminum alloy to improve its corrosion resistance.Then, the cold rolled steel sheet is cooled to room temperature to obtain cold rolled martensitic steel.

[0050] Example

[0051] The following tests, examples, graphical illustrations and tables presented herein are non-limiting in nature and must be considered solely for purposes of illustration and will demonstrate the advantageous features of the present invention.

[0052] Steel plates made of steels with different compositions are summarized in Table 1, wherein the steel plates were respectively produced according to the process parameters as noted in Table 2. Thereafter, Table 3 summarizes the microstructures of the steel plates obtained during the tests, and Table 4 summarizes the evaluation results of the obtained properties.

[0053]

[0054]

[0055]

[0056] Table 3 illustrates the results of tests carried out according to standards on different microscopes, such as a scanning electron microscope, for determining the microstructure in terms of area fraction for both the steel of the invention and the reference steel. The results are noted herein:

[0057] Table 3:

[0058]

[0059] I = according to the invention; R = reference; underlined values: not according to the invention.

[0060] Table 4

[0061] The results of various mechanical tests performed according to the standard are summarized. To test the ultimate tensile strength and yield strength, the ultimate tensile strength and yield strength were tested according to JIS-Z2241. To evaluate the hole expansion, a test called hole expansion was applied, in which the sample was punched (10 mm hole) and deformed, after which we measured the hole diameter and calculated HER% = 100*(Df-Di) / Di, where Df is the diameter measured in millimeters after deformation and Di is the diameter measured in millimeters before deformation.

[0062]

[0063] I = according to the invention; R = reference; underlined values: not according to the invention.

Claims

1. A martensitic steel plate comprising the following elements expressed in weight percentage: 0.07% ≦ C ≦ 0.12%; 1.9%≦Mn≦2.5%; 0.2%≦Si≦0.6%; 0.01%≦Al≦0.1%; 0.1%≦Cr≦0.5%; 0.2%≦Mo≦0.6%; 0.001%≦Nb≦0.1%; 0%≦S≦0.09%; 0% ≦ P ≦ 0.09%; 0%≦N≦0.09%; and can include one or more of the following optional elements: 0.001%≦Ti≦0.1%; 0.0005%≦B≦0.005%; 0%≦V≦0.1%; 0%≦Ni≦1%; 0% ≦ Cu ≦ 1%; 0%≦Sn≦0.1%; 0%≦Pb≦0.1%; 0%≦Sb≦0.1%; 0.001%≦Ca≦0.01%; The remainder of the composition consists of iron and unavoidable impurities caused by processing, and the microstructure of the steel consists of 80% to 94% tempered martensite and 6% to 20% fresh martensite in terms of area percentage.

2. The martensitic steel sheet according to claim 1, wherein the composition contains 0.25% to 0.5% silicon.

3. The martensitic steel sheet according to claim 1 or 2, wherein the composition contains 0.08% to 0.11% carbon.

4. The martensitic steel sheet according to any one of claims 1 to 3, wherein the composition contains 2.0% to 2.4% manganese.

5. The martensitic steel sheet according to any one of claims 1 to 4, wherein The amount of fresh martensite is 6% to 18%.

6. The martensitic steel sheet according to any one of claims 1 to 5, wherein a hole expansion ratio of the steel is 40% or more.

7. A method for producing a martensitic steel sheet, comprising the following steps in sequence: - Providing a steel composition according to any one of claims 1 to 4; - reheating the semi-finished product to a temperature of 1000° C. to 1280° C.; - rolling the semi-finished product in the austenite range to obtain a hot-rolled steel plate, wherein the hot rolling end temperature is Ac3 to Ac3+100°C; - cooling the plate to a coiling temperature below 675°C at a cooling rate of at least 10°C / sec; and coiling the hot rolled plate; - cooling the hot rolled sheet to room temperature; - optionally subjecting the hot rolled steel sheet to a descaling process; - optionally the hot rolled steel sheet can be annealed; - optionally subjecting the hot rolled steel sheet to a descaling process; - cold rolling the hot rolled steel sheet at a reduction ratio CR of 35% to 90% to obtain a cold rolled steel sheet; - then heating the cold rolled steel sheet from room temperature to a temperature T of Ac3 to Ac3+100°C at a heating rate HR1 of at least 1°C / s; keeping the cold rolled steel sheet at the temperature T for a period of 10 to 500 seconds; - then cooling the cold rolled steel sheet from T soak to a temperature T1 of Ms to Ms-100°C at a cooling rate CR1 of 1°C / s to 150°C / s; - then the cold rolled steel sheet is kept at temperature T1 for a period of 5 to 100 seconds; - then reheating the cold rolled steel sheet to a tempering temperature Ttempering of 400° C. to 550° C. at a rate of at least 1° C. / second, and maintaining the cold rolled steel sheet at the tempering temperature for a period of 10 seconds to 600 seconds; - Then cooled to room temperature at a cooling rate of at least 1°C / sec to obtain a martensitic steel sheet.

8. The method of claim 7, wherein the coiling temperature is 475°C to 675°C.

9. The method according to claim 7 or 8, wherein Tsoak is Ac3 to Ac3+50°C.

10. The method according to any one of claims 7 to 9, wherein CR1 is 20°C / sec to 120°C / sec.

11. The method according to any one of claims 7 to 10, wherein T1 is Ms to Ms-70°C.

12. The method according to any one of claims 7 to 11, wherein the cold rolled steel sheet is maintained at the T1 temperature for a period of 5 to 50 seconds.

13. The method according to any one of claims 7 to 12, wherein the heating rate to the temperature Ttemper is at least 2°C / s.

14. The method according to any one of claims 7 to 13, wherein T temper is 420°C to 500°C.

15. Use of a steel sheet obtainable according to any one of claims 1 to 6 or manufactured according to the method of any one of claims 7 to 14 for manufacturing structural parts of a vehicle.

Citation Information

Cited By

  • Low-yield-ratio 980MPa-grade cold-rolled martensitic steel for automobiles and preparation method of 980MPa-grade cold-rolled martensitic steel

    CN121204538A